Aktivitas Sexting melalui Aplikasi Anonim: Studi Kasus : 5 pengguna akun Whisper - Wulandari, Retno; Rinanta Sari, Dian (Saskara : Indonesian Journal of Society Studies, 2022)
This study aims to look at the problems in cybersex crime, one of which is Sexting activity, namely sexual behavior on mobile phones (phone sex), which is currently happening, especially in anonymous-based applications. This study aims to describe the motives for using the Whisper application, then how the process is to form a Sexting activity message, and what social impact is felt by Whisper account users. They use the Whisper application because Whisper is an anonymous-based application that is a place or place for users to do Sexting activities. Where Whisper has a chat rating for each user and always maintains the privacy of its users. Sexting itself is the activity of sending messages in the form of text, or photos through Roomchat social media. They chat using language that leads to sex, or send sex-related pictures to provoke their sexual fantasies. So they can imagine the fantasy and do masturbation and masturbation. On the other hand, the development of digital technology has brought human fantasy to the limit, creating three-dimensional spaces as if humans stepped from the real world to the fantasy world, a virtual world that looks real. When technology satisfies human desires/lusts, giving the charm of ecstasy, then moral values ​​seem to fall out one by one. Communication through the media keeps people trapped in simulation games that have nothing to do with reality. This situation is what Jean Baudrillard calls hyperreality. Imaging makes humans seem to come out of the real world and enter a fantasy world, a virtual world that looks very real. There's a simulation process there, full of visual manipulation.